Genetic Basis of Response of Ghanaian Local Chickens to Infection With a Lentogenic Newcastle Disease Virus - Walugembe, Muhammed; Amuzu-Aweh, Esinam N.; Botchway, Princess K.; Naazie, Augustine; Aning, George; Wang, Ying; Saelao, Perot; Kelly, Terra; Gallardo, Rodrigo A.; Zhou, Huaijun; Lamont, Susan J.; Kayang, Boniface B.; et al. (Frontiers in Genetics, 2020)
Newcastle Disease (ND) is a global threat to domestic poultry, especially in developing countries, where entire small-holder flocks are often lost to the disease. Local chicken ecotypes are important to rural households and provide high-quality protein in meat and eggs. To investigate the genetics of Ghanaian local chicken ecotypes to Newcastle Disease virus (NDV), three popular Ghanaian chicken ecotypes (regional populations) were challenged with a lentogenic strain of NDV at 28 days of age. NDV response phenotypes, including anti-NDV antibody levels (pre-infection and 10 days post-infection (dpi)), and viral load (2 and 6 dpi) were measured, in addition to growth rate following infection. Genetic parameters were estimated and two genome-wide association study analysis methods were used on data from 1,440 chickens that were genotyped on a chicken 600K Single Nucleotide Polymorphism (SNP) chip. Heritability estimates were moderate to high (0.23-0.55) for all traits. Twelve quantitative trait loci (QTL) for growth and/or response to NDV from single-SNP analyses and 20 genomic regions explaining ≥ 1% of genetic variance detected by Bayes B method were identified. Seven QTLs, containing one SNP from the single SNP analyses corresponded in location with a 1-Mb window explaining >1% genetic variance for growth rate, anti-NDV antibody levels, and viral load at 2 and 6 dpi. An important gene for growth during stress, CHORDC1 associated with post-infection growth rate, and other immune related genes such as VAV2, IL12B, DUSP1, and IL17B were identified as positional candidate genes. The moderate to high estimates of heritability and identified QTL suggest that host response to NDV can be improved through selective breeding of Ghanaian local chicken ecotypes to enhance increased NDV resistance and vaccine efficacy.